An Immersive Journey Through Early Electronic Works of… NHK Studios - Parra Cancino, Juan; An Immersive Journey Through Early Electronic Works of… NHK Studios Koetshuis Orpheus Instituut June 10 2024 (2024)
Tape, Vinyl, and digital, multichannel fixed support pieces, presented in their original formats.
Listening sessions of Early Electronic Music
FRIS
0
Keywords: Music, Thought and Technology